(untitled) (Journal of Cancer Research Updates, 2020)
Acute myeloid leukemia (AML) is a clinical and genetic heterogeneous disease with a poor prognosis. Recent advances in genomics and molecular biology have immensely improved the understanding of disease. The advantages of syndrome differentiation and treatment are strong selectivity, good curative effect and lesser side effects. In recent years, according to the molecular mechanism of acute myeloid leukemia, many new therapeutic targets have been found. New targets of differentiation therapy in recent years, such as cell cyclin-dependent kinase (CDK2), isocitrate dehydrogenase (IDH1, IDH2), Homeobox genes (HoxA9), Dihy-droorotate dehydrogenase (DHODH) and some others, are reviewed in this article.